Diagnostic accuracy of Mycobacterium tuberculosis-specific triple-color FluoroSpot assay in differentiating tuberculosis infection status in febrile patients with suspected tuberculosis - Zhang, Lifan; Li, Yuanchun; Zou, Xiaoqing; Ma, Huimin; Gao, Mengqiu; Ge, Qiping; Zhang, Yueqiu; Yang, Zhengrong; Song, Xinuo; Yang, Qiwen; Liu, Xiaoqing (Frontiers in Immunology, 2025)
ObjectiveThis study aims to evaluate the diagnostic accuracy of a Mycobacterium tuberculosis (MTB)-specific triple-color FluoroSpot assay (IFN-γ/IL-2/TNF-α) in the differentiation of tuberculosis (TB) infection status in febrile patients.MethodFebrile patients with suspected active TB (ATB) were consecutively enrolled. The frequencies and proportions of MTB-specific T cells secreting IFN-γ, IL-2, and TNF-α were detected at the single-cell level by triple-color FluoroSpot assay. The diagnostic index was fitted with a binary logistic regression model, and the diagnostic accuracy was evaluated according to the receiver operating characteristic (ROC) curve. The sensitivity, specificity, predictive values (PV), and likelihood ratios (LR) were calculated.ResultA total of 210 febrile patients were enrolled, 53 patients were diagnosed with ATB (28 pathogen-confirmed vs. 25 clinically diagnosed) and 157 patients were non-ATB (84 with latent tuberculosis infection (LTBI) vs. 73 uninfected with MTB). Additionally, 30 pathogen-confirmed ATB patients were assembled. When diagnosing ATB, the area under the ROC curve (AUROC) of the MTB-specific triple-color FluoroSpot assay was significantly better than that of T-SPOT.TB (0.882 vs. 0.811, p = 0.017). With the fitted diagnostic index at a cutoff value of 0.378, the sensitivity, specificity, LR+, and LR- were 74.7%, 93.0%, 10.66, and 0.27, respectively. When differentiating ATB from LTBI, the AUROC of the FluoroSpot assay and T-SPOT.TB was 0.878 and 0.692, respectively (p < 0.001). With a diagnostic index of 0.413, the sensitivity, specificity, LR+, and LR were 77.1%, 85.7%, 5.40, and 0.27, respectively.ConclusionThe MTB-specific triple-color FluoroSpot (IFN-γ/IL-2/TNF-α) might be helpful for the differentiation of TB infection status in febrile patients.